A PORTRAIT OF ENGLISH LANGUAGE TEACHING IN ELEMENTARY SCHOOL BY NON-ENGLISH MAJOR TEACHERS - Tri Achmad Efendi; Sri Nurhidayah; Apsari Fajar Prihantini (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Balikpapan, 2024)
This research analyzes Teaching English in elementary schools plays a pivotal role in shaping the language skills of young learners. Unfortunately, it is a common case that in Indonesia that a school doesn’t have English teachers, and homeroom teachers have to teach English. Therefore, this study delves into investigating the teaching and learning in one of the elementary schools that has no English teachers. In addition, it strived to seek out the challenges faced by non-English major teachers in the school under study as well as portray their English teaching practice. Further, this study explored strategies to improve their professional development in English language instruction. Through a qualitative research approach, including questionnaires and focus group discussions (FGD), The findings highlighted mostly the teachers who graduated from PGSD confirmed that they faced difficulty using English as a means of classroom communication. Additionally, it was found that listening as a receptive skill is neglected, as are communicative activities. The participants shared that grammar was mostly taught, although they mentioned they had difficulty with it. The implications of this research extend to curriculum design, pedagogical practices, and policy recommendations aimed at enhancing the quality of English language education for young learners in diverse educational settings.